A proposal for the reform of the Hospital in the Late Thirteenth Century - Forey, Alan (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2017)
Although opposition to masters was voiced in several military orders in the thirteenth century, the criticism expressed in the Hospital in 1295 was unusual in that an attempt was made to alter the order’s structure of government. It was claimed that masters had not observed the rule and customs of the order, and the Hospital was therefore to be placed under the control of seven diffinitors, of whom the master was to be one, and who were to hold office for life: they were to constitute a self-perpetuating oligarchy. Their proposed powers were to be noticeably greater than those of diffinitors of other religious orders, as the latter usually exercised authority only during provincial or general chapters. Support for the scheme quickly waned, however, and it was not implemented; nor was any attempt made later to revive it. Its failure reflects the widespread acceptance of a strong monarchical form of government, and can be compared with the failure of measures taken in various countries during the late thirteenth and early fourteenth centuries to restrict the independence of secular rulers when these were pursuing policies which were unpopular or unsuccessful.